Optimization of bead milling parameters for the cell disruption of microalgae: Process modeling and application to Porphyridium cruentum and Nannochloropsis oculata. (November 2015) - Montalescot, V.; Rinaldi, T.; Touchard, R.; Jubeau, S.; Frappart, M.; Jaouen, P.; Bourseau, P.; Marchal, L.
Highlights: Continuous bead milling disruption was tested for two valuable microalgal strains. Residence Time Distribution in the grinding chamber corresponded to a 2-CSTR model. Hydrodynamics was taken into account for first order kinetics disruption modeling. Stress modeling was successfully adapted to microalgae. N. oculata was more resistant regarding pressure and bead milling than P. cruentum . Abstract: A study of cell disruption by bead milling for two microalgae, Nannochloropsis oculata and Porphyridium cruentum, was performed. Strains robustness was quantified by high-pressure disruption assays. The hydrodynamics in the bead mill grinding chamber was studied by Residence Time Distribution modeling. Operating parameters effects were analyzed and modeled in terms of stress intensities and stress number. RTD corresponded to a 2 CSTR in series model. First order kinetics cell disruption was modeled in consequence. Continuous bead milling was efficient for both strains disruption. SI–SN modeling was successfully adapted to microalgae. As predicted by high pressure assays, N. oculata was more resistant than P. cruentum . The critical stress intensity was twice more important for N. oculata than for P. cruentum . SI–SN modeling allows the determination of operating parameters minimizing energy consumption and gives a scalable approach to develop and optimize microalgal disruption by bead milling.